PENGARUH PIJAT BAYI TERHADAP PENINGKATAN BERAT BADAN BALITA USIA 3-6 TAHUN DI PMB NY.”S” SIDOARJO - Anjas Sari, Wahyu; Tri Sumini, Gempi (LPPM STIKES HUSADA JOMBANG, 2023)
Growth has a direct and indirect effect on the development of toddlers. Weight gain and loss must be considered at a young age. Increased body weight indicates a good nutritional status. Good nutritional status can be achieved when the body gets enough nutrients that are strong enough to allow physical growth to occur. Stimulation or stimulation in the form of touch therapy and massage also affects weight gain. Experts have proven that touch and massage therapy produces beneficial psychological changes in the form of increased growth, increased endurance, and better emotional intelligence. Baby massage is a fun way to relieve tension and fussiness. Because a gentle massage will help relax the muscles so that he becomes calm and falls asleep The design of this research is analytic with a pre-experimental approach, with sampling using the Purposive Sampling Technique, the number of respondents is 31 toddlers. Data analysis was performed univariate and bivariate with Wilcoxon test (ɑ = 0.05). From the analysis, the results of the Wilcoxcon sign rank test statistical test with an error rate of : 0.05 with the help of SPSS software showed that the p value (value) was 0.00 < (0.05). These results indicate that H0 is rejected, which means that there is an effect of baby massage on weight gain in toddlers aged 1-5 years. conducted at PMB Ny.S Surabaya in 2022.